Optimalisasi Mutu Pelayanan Kesehatan Preventif Berbasis Thibbunnabawi melalui Pemanfaatan Sistem Informasi - Yanto Saputra; Dina Mardiati; Adhamdi Tria Putra Abza; Muhammad Muhammad; Purjumatin Purjumatin (Forum Kerjasama Pendidikan Tinggi, 2026)
The community service partner was a holistic cupping clinic that provides preventive and complementary health services based on Thibbunnabawi but still faced limitations in service administration and documentation. The partner's main problems included non-digital patient records, manual cupping schedules, inconsistent therapy records, non-integrated initial screening, verbally delivered preventive education, and service reports that were difficult to summarize for internal evaluation. This activity aimed to optimize the quality of preventive health services through the utilization of a Holistic Cupping Clinic Information System designed according to the work needs of clinic managers, administrators, therapists, and assistants. The implementation method consisted of needs observation, partner interviews, system design, application implementation, user training, practical mentoring, and activity evaluation. Ten participants were involved, with an average initial digital literacy score of 54.1. The results showed improvement in all service indicators: patient data input increased from 42 to 88, cupping scheduling from 40 to 86, therapy records from 45 to 84, initial screening from 50 to 87, preventive education from 56 to 90, and service reporting from 38 to 82. Participant satisfaction was also high, including system usability at 92 percent, perceived service benefits at 95 percent, training clarity at 93 percent, feature suitability at 90 percent, and intention for continued use at 88 percent. The contribution of this activity lies in providing a simple, contextual, and applicable information system utilization model to strengthen administration, service safety, therapy documentation, and preventive education in holistic cupping clinics. This contribution gives the partner a clearer digital workflow to support service continuity.